MANAJEMEN LINGKUNGAN PENDIDIKAN DALAM PERSPEKTIF PERUBAHAN IKLIM DI INDONESIA - Hari Nur Cahya Murni (Postgraduate, University of Mataram, 2024)
Education has been managed in such a way that the maximum educational goals can be achieved. In its implementation, education is certainly inseparable from management and its surrounding environment. In management, the presence of the right strategy and a solid team is needed so that the goals can be achieved. Meanwhile, the strategy in management itself only reacts to the human-shaped environment, which is society. Both management and the school environment have strong interactions and influences on the education management process. Educational institutions' management must ensure that their methods are in line with societal demands, as social and cultural institutions have a significant impact on how the institution operates. The educational environment should be managed in such a way that the educational goals can be achieved. With good interaction and support from the community and parties related to the educational environment, it is hoped that schools will advance. In other words, good cooperation from lecturers, parents, education boards, committees, and the community around the school environment is believed to be able to develop potential and improve the quality of education.